Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00420-007-0227-7
|View full text |Cite
|
Sign up to set email alerts
|

Hearing status after an industrial explosion: experience of the AZF explosion, 21 September 2001, France

Abstract: The study demonstrated statistically significant hearing shift from 2,000 to 6,000 Hz in relation with distance from the explosion and showed that even when functional symptoms were present, people did not necessarily seek medical advice. Screening for hearing loss should be recommended for people most exposed to excess acoustic pressure, in order to offer them prevention advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Having increased hearing threshold due to acoustic trauma might lead people to be more susceptible to noise. 25,26 Systemic ototoxic drug, streptomycin was taken by one as a part of anti-tuberculosis treatment. This may act synergistically with noise to worsen hearing loss.…”
Section: Original Articlementioning
confidence: 99%
“…Having increased hearing threshold due to acoustic trauma might lead people to be more susceptible to noise. 25,26 Systemic ototoxic drug, streptomycin was taken by one as a part of anti-tuberculosis treatment. This may act synergistically with noise to worsen hearing loss.…”
Section: Original Articlementioning
confidence: 99%
“…In view of the extent of the industrial disaster and its impact, an epidemiological follow-up program was set up [29]. The data returned by health surveillance systems and surveys suggested hearing problems and an impact on the mental health of the population of Toulouse in the days and weeks following the explosion [29,39,40]. Because of the consequences for the working population, a cross-sectional survey was carried out in this population to determine prevalence and predictors of PTSD 12 months after the explosion.…”
Section: Introductionmentioning
confidence: 99%
“…For example, after the AZF explosion in Toulouse, France in 2001, an epidemiological study indicated that many survivors had hearing problems due to the explosion; this information was used to recommend a screening of hearing loss in the population around the site of the explosion. 15…”
Section: Methodsmentioning
confidence: 99%